Need for Revitalization in Nepal’s Role at the United Nations and Non-Aligned Movement - Karki, Nir Bahadur (NCWA Annual Journal, 2024)
The formulation, execution and promotion of foreign policy to safeguard its independence, sovereignty and territorial integrity and promote relations for mutual benefit with neighboring and other friendly countries for enhancing national image abroad is the responsibility of Nepal’s government. Garnering support for any scheme of national interest by way of developing strategic foreign policy and implementing it through diplomatic maneuvers to negotiate with other countries in response to the changing context is also its duty. Each country has its way of managing its international relations as the changes in world affairs are dynamic with time. Nepal is one of the oldest countries in the world where no foreign flag is ever flown. It has been adopting its foreign policy mainly in line with the vision of the founder of the nation, late King Prithvi Narayan Shah the great who foresaw the geopolitical implications, challenges and opportunities and had emphasized the need for a carefully formulated strategy in running foreign affairs. Since the world has been witnessing changes at a fast speed, Nepal needs to be more equipped as the current performance appears less result-oriented in comparison with the past ones. Since Nepal’s representation at the United Nations and Non-aligned Movement are considered suitable venues for pleading and presenting the country’s perspectives, the government of Nepal needs better efforts than what is prevailing at present.